Literary Ecocritical on the Novel Rahasia Pelangi By Riawani Elyta and Sabrina WS - Diaul Khaerah; Amayma Abdelali; Geanky O. Malinano (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to identify and describe the forms of environmental wisdom portrayed in the novel Rahasia Pelangi by Riawani Elyta and Sabrina Ws through an ecocritical perspective. Methodology: This research employed a qualitative descriptive method using an ecocriticism approach. The data source was the novel Rahasia Pelangi. The tools used included data reduction sheets, data presentation tables, and verification guides following Miles and Huberman’s qualitative analysis model. No software was used. Main Findings: The study revealed twenty-two forms of environmental wisdom represented in the narrative. These findings were categorized into five aspects: respect for nature, moral responsibility toward nature, solidarity with nature, affection and care for nature, and attitudes that avoid disturbing natural life. These categories show how the novel embeds ecological awareness through character actions and narrative events. Novelty/Originality of this study: This study provides a new contribution by applying literary ecocriticism to explore environmental wisdom within an Indonesian popular novel that has rarely been analyzed from this perspective. It advances knowledge by mapping ecological moral values in narrative structures and offering a model for identifying environmental ethics in contemporary Indonesian fiction.